2019
DOI: 10.1021/acs.jafc.9b03323
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Alternatives to Returning All Crop Residues as Biochar to the Crop Field? A Three-Source 13C and 14C Partitioning Study

Abstract: The simultaneous effects of biochar on soil organic matter (SOM, C4) and sweet potato (SP) residue (Ipomoea batatas, C3) mineralization were studied over 180 days via 13C and 14C isotopic label partitioning. Upon concomitant SP residue addition, biochar mineralization decreased by 11% of the total added biochar-C. Compared to positive priming effects induced by biochar amendment alone on SOM (0.46 mg C g–1 soil) at 180 days, amendment solely with SP residues induced significantly larger effects (1.5 mg C g–1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The release of volatiles at high temperatures may explain the impact of pyrolysis temperature on such characteristics. According to many researchers [27][28][29], higher pyrolysis temperatures resulted in a larger biochar surface area, higher pH, and higher percent C content but lower percent N content. As a result, choosing an appropriate pyrolysis temperature involves a tradeoff between the specified surface and chemical characteristics [27][28][29].…”
Section: Biochar Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of volatiles at high temperatures may explain the impact of pyrolysis temperature on such characteristics. According to many researchers [27][28][29], higher pyrolysis temperatures resulted in a larger biochar surface area, higher pH, and higher percent C content but lower percent N content. As a result, choosing an appropriate pyrolysis temperature involves a tradeoff between the specified surface and chemical characteristics [27][28][29].…”
Section: Biochar Preparation Methodsmentioning
confidence: 99%
“…According to many researchers [27][28][29], higher pyrolysis temperatures resulted in a larger biochar surface area, higher pH, and higher percent C content but lower percent N content. As a result, choosing an appropriate pyrolysis temperature involves a tradeoff between the specified surface and chemical characteristics [27][28][29].…”
Section: Biochar Preparation Methodsmentioning
confidence: 99%
“…There have been various studies in which BC produced at lower temperature ranging from 450 to 550 • C stimulated positive priming when added to sandy loam (Table 3). Overall, BC promoted increases in C sequestration, organic carbon retention, SOM, mineralization, phosphorous and potassium content, and plant biomass [136][137][138][139]. Conversely, one study reported a decrease in soil microbial biomass and SOM mineralization when crop residue-derived BC (450 • C) was applied to sandy loam soil [140].…”
Section: Soil Organic Matter (Som)mentioning
confidence: 99%